Advanced maternal age and adverse pregnancy outcomes in Muar, Johor, Malaysia - Herny Erdawati Mohd Rashed; S. Maria Awaluddin; Noor Ani Ahmad; Nurul Huda Md Supar; Zubidah Md Lani; Fauziah Aziz; Kamarul Ariffin Sulaiman; Rafedah Masengat; Nur Intan Mohd Ithnin; Zulkipli Othman; Tahir Aris (Penerbit Universiti Kebangsaan Malaysia, 2016)
Various factors may contribute to adverse pregnancy outcomes; either maternal or foetal outcomes. This study aimed was to determine the association between advanced maternal age and adverse pregnancy outcomes. This is a cross sectional study. Data were collected from the birth records from January 1st 2012 until December 31st 2012 in Muar District. Descriptive and multiple logistic regression analyses were done and the results were presented as adjusted odds ratio (aOR) with p-value <0.05. The proportion of birth in Muar district, Johor was 14.8% among mothers aged 35 years and older and 85.2% among mothers aged 20 to 34 years. Advanced maternal age was associated with pregnancy-induced hypertension (aOR: 5.00; 95%CI: 1.95-12.65), gestational diabetes mellitus (aOR: 2.32; 95%CI: 1.35-4.00) and Caesarean section (aOR: 2.21; 95%CI: 1.53-3.19). Anaemia was negatively associated with advanced maternal age (aOR: 0.50; 95%CI: 0.32-0.78). No significant association was found between advanced maternal age and adverse foetal outcomes. In view of the findings, special attention should be paid to the antenatal mothers aged 35 years and older, even to those without any pre-existing medical problems.